2005
DOI: 10.1097/01.bsd.0000169063.84628.fe
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Excitability in Patients With Chronic Low Back Pain

Abstract: In summary, this study has revealed that corticospinal excitability, driving ES muscles close to the site of pain, is lowered in patients with chronic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 45 publications
11
110
2
3
Order By: Relevance
“…In another study (study V), I demonstrated that the presence of low back pain is associated with more generalised hyperalgesia, in keeping with the results from other studies 45,78,176,177 . In the context of back pain patients undergoing back surgery (I, VI), I also found that the presence and degree of preoperative low back pain influenced the incidence -but not the degreeof generalised hyperalgesia in the first postoperative week 178 .…”
Section: Preoperative Factors and Postoperative Pain Outcomessupporting
confidence: 74%
“…In another study (study V), I demonstrated that the presence of low back pain is associated with more generalised hyperalgesia, in keeping with the results from other studies 45,78,176,177 . In the context of back pain patients undergoing back surgery (I, VI), I also found that the presence and degree of preoperative low back pain influenced the incidence -but not the degreeof generalised hyperalgesia in the first postoperative week 178 .…”
Section: Preoperative Factors and Postoperative Pain Outcomessupporting
confidence: 74%
“…TMS studies conducted in other types of MSK disorders have also shown alterations in corticospinal excitability, with some reporting reductions in excitability and others reporting increases Strutton et al, 2003;Strutton et al, 2005). Some studies have also reported disruption in intracortical inhibition in patients with low back pain and complex regional syndrome type 1 (Masse-Alarie et al, 2012;Schwenkreis et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…The single-and double-pulse TMS paradigms were used for the testing of corticomotor excitability and intracortical motor inhibition, respectively, because they were two important indicators of M1 functional integrity. We hypothesized delays in TrA/IO anticipatory activation with a reduction in the duration of anticipatory co-activation in LBP patients, along with changes in TMS outcomes, given the known absence of M1 inhibition in chronic pain (Lefaucheur et al 2006) and the decrease in M1 excitability in individuals with unilateral sciatica and chronic LBP (Strutton et al 2005;Strutton et al 2003).…”
Section: Introductionmentioning
confidence: 99%